A Chimeric Peptide Derived from a Bacterial Effector Protein Attenuates TLR-2/4-Mediated Production of Pro-Inflammatory Cytokines and Enhances the Cellular Availability of Gentamicin - Nandi BR; Patra B; Radhakrishnan GK (Journal of Inflammation Research)
Binita Roy Nandi,1,2 Biswaranjan Patra,1,2 Girish K Radhakrishnan1 1Laboratory of Bacterial Pathogenesis, National Institute of Animal Biotechnology, Hyderabad, Telangana, 500032, India; 2Regional Centre for Biotechnology (RCB), Faridabad, 121001, IndiaCorrespondence: Girish K Radhakrishnan, Email girish@niab.org.inIntroduction: Toll-like receptors (TLRs) are critical components of innate immunity, recognizing microbe-derived molecules and triggering pro-inflammatory cytokine production for pathogen clearance. However, TLR hyperactivation can cause excessive inflammation, contributing to disorders such as sepsis. Thus, modulating TLR signalling is a promising therapeutic strategy. The intracellular bacterial pathogen, Brucella, encodes TcpB, a cell-permeable anti-inflammatory protein that inhibits TLR2/4 signalling by targeting adaptor proteins TIRAP and MyD88. TcpB has an N-terminal phospholipid-binding motif conferring cell permeability and a C-terminal TIR domain for TLR interference. This study explores TcpB-derived peptides and evaluates their potential for therapeutic and research applications.Methods: We synthesized TcpB-derived peptides and evaluated their cytotoxicity, cell permeability, and anti-inflammatory effects using LDH assay, fluorescence microscopy, ELISA, and qRT-PCR. A chimeric peptide, TB4-BBL2, was then generated and evaluated for cellular uptake, interaction with TLR adaptors, and functional activities. Binding of FAM-labelled TB4-BBL2 to FLAG-tagged TIRAP/MYD88 was confirmed via co-immunoprecipitation and fluorescence analysis, while degradation of adaptors was assessed by Western blotting. The anti-inflammatory efficacy of TB4-BBL2 was evaluated in a murine endotoxemia model by measuring serum TNF-α and IL-6 levels using ELISA, and cytokine transcript levels in major organs using qRT-PCR. Additionally, TcpB-derived peptides conjugated to gentamicin were analyzed for enhanced intracellular delivery, bacterial clearance, and anti-inflammatory effects using CFU enumeration, ELISA, and qRT-PCR in both in vitro and in vivo.Results: TB4-BBL2 peptide was efficiently internalized by macrophages via endocytosis and promoted the degradation of TIRAP and MYD88, thereby attenuating TLR2/4-mediated pro-inflammatory cytokine production and oxidative stress. In vivo, TB4-BBL2 treatment resulted in over a 70% reduction in serum TNF-α levels, which was also reflected by decreased transcript levels in spleen tissue. Conjugation of TcpB-derived peptides to gentamicin enhanced its cell permeability and facilitated efficient elimination of intracellular bacteria. This was corroborated by enhanced bacterial clearance in CFU assays, showing over a 2-Log reduction in vivo along with more than an 80% decrease in splenic TNF-α transcripts in the murine model of brucellosis.Discussion: Our findings highlight the therapeutic potential of TcpB-derived peptides in modulating TLR-mediated inflammation and enhancing intracellular antibiotic delivery. This dual-functional strategy offers a promising novel approach for treating inflammatory diseases and persistent intracellular infections, warranting further investigation toward clinical applications. Keywords: inflammation, TLR2/4, pro-inflammatory cytokines, inflammatory disorders, peptide-based drugs, Brucella, endotoxemia, cell-permeable antibiotics